STRUKTUR KOMUNITAS IKAN DI SUNGAI LULAK DAN SUNGAI GENDIR KABUPATEN BANGKA BARAT - Aditia Adit; Wahyu Adi; Andi Gustomi (Akuatik: Jurnal Sumberdaya Perairan, 2020)
ABSTRACT Aditia (2021611001) The Community Structure of Fish in Lulak Stream and Gendir Stream of West Bangka Regency. (Supervisors: Wahyu Adi, S.Pi.,M.Si dan Andi Gustomi, S.Pi.,M.Si) The waters of the stream in west Bangka nowadays facing the threat of the deforestation or the fragmentation of the alteration of land function such as for the plantations, agriculture mostly for the program of rice field print that makes the forest area and the watershed threaten the fish habitats, for instance the Lulak stream and gendir stream in Kelapa, West Bangka regency. The goals of this study is to examine the diversity of the fish, examine the community structure and examine the relation between the waters quality with the fish diversity in Lulak Stream and Gendir Stream. The data was took and conducted in February 2020 using the gill net and dip net. The result showed that the diversity value has the index with the amount is 1,948 for Lulak Stream and 1,881 for Gendir Stream with the category is moderate. The community structure of fish in Lulak stream and Gendir stream was dominated by Cyprinidae with 5 species from 14 species based on what was found in both of the stream. There was 14 fish with 12 of fish species found in Lulak stream and 11 fish in Gendir stream that dominated by cyprinidae ( Puntius binotatus, Puntius lineatus, Cyclocheilichthys apogon dan Rasbora chepholataenia). The Physic and Chemistry factors in Lulak Stream and Gendir Stream supports the survival life of the cyprinidae that dominate both of the river. Keywords: Diversity, Fish , Stream, fresh waters, West Bangka